2013
DOI: 10.1038/srep01255
|View full text |Cite
|
Sign up to set email alerts
|

Scanning acoustic microscopy for characterization of neoplastic and inflammatory lesions of lymph nodes

Abstract: A scanning acoustic microscope (SAM) imaging system calculates and color codes speed of sound (SOS). We evaluated the SAM results for lymph node imaging and compared these results with those of light microscopy (LM). SAM showed normal structures and localized/diffuse lesions of the lymph node. Our results revealed that as a rule, soft areas such as cystic necrosis presented less SOS while harder areas such as coagulative necrosis, granulomas, and fibrosis exhibited greater SOS. SOS increased according to strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…At a frequency approximately higher than 300 MHz, individual cells can be resolved while at a frequency ranging from 1 to 1.5 GHz detailed information about their internal structure becomes apparent. [21][22][23] Liver carcinoma, gastric cancer, lesions of lymph nodes, breast and renal cancer were actively investigated by many research and groups 16,[24][25][26][27] showing that tumour tissues exhibit distinct sound speed and attenuation comparing to healthy tissues. The magnitude and indication of these pathological modification change for various tumour.…”
Section: Introductionmentioning
confidence: 99%
“…At a frequency approximately higher than 300 MHz, individual cells can be resolved while at a frequency ranging from 1 to 1.5 GHz detailed information about their internal structure becomes apparent. [21][22][23] Liver carcinoma, gastric cancer, lesions of lymph nodes, breast and renal cancer were actively investigated by many research and groups 16,[24][25][26][27] showing that tumour tissues exhibit distinct sound speed and attenuation comparing to healthy tissues. The magnitude and indication of these pathological modification change for various tumour.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid lymphomas showed a faster speed compared with lymphomas in other organs. 5,6 Fibrous capsules or bands around carcinomas were split (Figures 6 and 8-10), and surrounding follicles were angular or irregular with fragmented colloids.…”
Section: Resultsmentioning
confidence: 99%
“…SOS compared with lymphomas of other organs such as the stomach 5 and lymph nodes. 6 Rapidly growing tumors, such as the undifferentiated or poorly differentiated carcinomas, showed the slowest SOS, probably because of collagen-deficient stroma. From previous observations, carcinomas had slow SOS if few desmoplastic reactions occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAM has been applied successfully for characterizing various soft tissues and disease states [8]- [12]. However, only one study reported SAM measurements for human LN tissues [10]. The authors studied the distribution of speed of sound (c) of various tissue types with a resolution of 13 μm using a 120-MHz transducer.…”
Section: Introductionmentioning
confidence: 99%